Specification of problems from the business goals in the context of early software requirements elicitation (2014)
One of the main activities of the early elicitation of software requirements is the recognition and specification of organizational problems. Such activity is intended to allow for an initial requirements definition and the fulfillment of the stakeholder needs. Such problems can be directly traced to the organizational goals for achieving contextualized software applications and alignment with the organizational raison d'etre. In current elicitation methods based on goals and problems, the relationships are detected by the analyst and the stakeholder by using his/her experience and knowledge. However, traceability among goals and problems is still not achieved. In this paper we propose a method for specifying problems based on business goals. This method is composed by a set of semantic and syntactic rules used by the analyst for expressing the problem from the goal statements. Also, we present a laboratory example based on a KAOS goal diagram Keywords: Business goals; problems; semantic rules; syntactic rules.